Systems analysis of lactose metabolism in Trichoderma reesei identifies a lactose permease that is essential for cellulase induction. - Christa Ivanova; Jenny A Bååth; Bernhard Seiboth; Christian P Kubicek (PLoS ONE)
Trichoderma reesei colonizes predecayed wood in nature and metabolizes cellulose and hemicellulose from the plant biomass. The respective enzymes are industrially produced for application in the biofuel and biorefinery industry. However, these enzymes are also induced in the presence of lactose (1,4-0-ß-d-galactopyranosyl-d-glucose), a waste product from cheese manufacture or whey processing industries. In fact, lactose is the only soluble carbon source that induces these enzymes in T. reesei on an industrial level but the reason for this unique phenomenon is not understood. To answer this question, we used systems analysis of the T. reesei transcriptome during utilization of lactose. We found that the respective CAZome encoded all glycosyl hydrolases necessary for cellulose degradation and particularly for the attack of monocotyledon xyloglucan, from which ß-galactosides could be released that may act as the inducers of T. reesei's cellulases and hemicellulases. In addition, lactose also induces a high number of putative transporters of the major facilitator superfamily. Deletion of fourteen of them identified one gene that is essential for lactose utilization and lactose uptake, and for cellulase induction by lactose (but not sophorose) in pregrown mycelia of T. reesei. These data shed new light on the mechanism by which T. reesei metabolizes lactose and offers strategies for its improvement. They also illuminate the key role of ß-D-galactosides in habitat specificity of this fungus.